2005
DOI: 10.1002/chem.200500428
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry of Wine Polyphenolic C‐Glycosidic Ellagitannins Targeting Human Topoisomerase II

Abstract: Polyphenolic nonahydroxyterphenoyl-containing C-glycosidic oak ellagitannins are found in wine as a result of the aging of this beverage in oak-made barrels. Once in the slightly acidic wine (pH approximately 3-4), some of these complex natural products such as (-)-vescalagin (1), but not its C-1 epimer (-)-castalagin (2), can capture grape-derived nucleophilic entities such as ethanol, the flavanols catechin (10a) and epicatechin (10b), the anthocyanin oenin (13b), and the thiolic glutathione (16) to furnish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
164
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 141 publications
(180 citation statements)
references
References 83 publications
(44 reference statements)
12
164
1
3
Order By: Relevance
“…1) (Quideau et al, 2011). These derivatives were prepared from vescalagin or castalagin that was extracted and purified from oak wood according to previously published procedures (Quideau et al, 2003(Quideau et al, , 2004(Quideau et al, , 2005. We first tested the effect of these ellagitannins on the catalytic activity of purified human Top2␣ and Top2␤ as measured by the in vitro decatenation of kinetoplast DNA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1) (Quideau et al, 2011). These derivatives were prepared from vescalagin or castalagin that was extracted and purified from oak wood according to previously published procedures (Quideau et al, 2003(Quideau et al, , 2004(Quideau et al, , 2005. We first tested the effect of these ellagitannins on the catalytic activity of purified human Top2␣ and Top2␤ as measured by the in vitro decatenation of kinetoplast DNA.…”
Section: Resultsmentioning
confidence: 99%
“…In the search for new topoisomerase II inhibitors originating from plants, a previous study investigated the ability of 60 compounds from the four main classes of tannins, gallotannins, ellagitannins, complex tannins, and condensed tannins, to inhibit human topoisomerase II in vitro and identified 36 derivatives that could inhibit Top2 with a higher potency than that of etoposide . More recently, we also found that new polyphenolic C-glucosidic ellagitannins isolated from wine aged in oak barrels could also inhibit Top2 with high potency (Quideau et al, 2005). However, the specificity of these ellagitannins toward Top2␣ or Top2␤ was never addressed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of flavano-ellagitannins (9-12) and the ß-1-O-ethylvescalagin (13) in red wines aged in oak barrels has been reported [14][15][16][17][18] (Fig. 1).…”
Section: Introductionmentioning
confidence: 93%